A participatory approach for tree diversification in cocoa farms: Ghanaian farmers experience - Asare, R.; Asare, R.A. (2008)
In Ghana, the diversity and density of non-cocoa trees in cocoa farms is primarily the result of farmers’ managing natural processes of regeneration in forest-fallow systems. Tree diversity is therefore more a result of haphazard, uncoordinated decisions over a long period rather than advanced planning. Relying on natural regeneration processes greatly limits farmers’ ability to select desirable species or arrange their distribution within farms. As a result, the potential of diverse cocoa growing systems is limited in its ability to make significant contributions to household incomes or conservation of biodiversity on farm and in the surrounding landscape. This paper presents a six step tree diversification process that was developed and implemented with farmers in Amansie West and Atwima Mponua districts of Ghana’s Ashanti Region using a participatory action learning approach. In conjunction with 36 farmers in six farmer groups, a tree diversification framework was tested and implemented. Farmers used the framework to critically characterize and select desirable non-cocoa trees according to biophysical and socio-economic attributes, and then planted these species onto farms with the aim of providing favorable vegetative cover for cocoa, as well as securing valuable sources of timber and non-timber products. In total, 960 tree seedlings were planted on 31 farms using a designed 12 m x 12 m triangular planting arrangement with an initial planting density of 28 trees per acre. The value of this process is that it provides farmers with a flexible decision support tool for evaluating and integrating desirable trees into tree crop systems for increased diversity.